Kikuchi-Fujimoto disease with multiple extra-nodal features - A clinical mimic - C.A. Mansoor; Z. Shemin (Reumatismo, 2019)
Extranodal involvement in Kikuchi’s disease is uncommon. A 31-year-old previously healthy Indian woman was admitted with high grade fever, multiple joint pain and skin rash for 3 weeks. She had negative anti-nuclear antibodies and had features of Kikuchi’s disease on lymph node biopsy. She also had multiple extranodal manifestations including erythematous maculopapular rash, symmetric polyarthritis and hepatosplenomegaly. Kikuchi’s disease with extranodal involvement can clinically mimic diseases like hematological malignancies, connective tissue disorders and certain infections. A lymph node biopsy plays a crucial role in making an accurate diagnosis by excluding other diseases. A discussion on the importance of differentiating Kikuchi’s disease from systemic lupus erythematosus is included.